A Review: Accumulation of Toxic Metals among Meat from Different Species - Morshdy, Alaa Eldin M.; Taha, Shaimaa; El Gohary, Amr E.; El Bayomi, Rasha M.; Hussein, Mohamed A. (Journal of Advanced Veterinary Research, 2023)
Meat contamination is a problem that must be addressed since it can affect consumers' health. Standard acceptable limits for heavy metals in meat and organs have been established by many international organizations. Livestock including sheep, cattle, camels, and goats side by side with other poultry species are the most significant sources of meat for protein. Heavy metal contamination in animal products may be harmful to people's health. The earth's crust naturally contains heavy metals, but uncontrolled human activity has significantly changed their geochemical cycles and biological equilibrium. This causes a buildup of metals in animal tissue that contain secondary metabolites, which gives rise to a specific pharmacological action. Humans can have negative health effects from prolonged exposure to heavy metals as lead, cadmium, arsenic, and mercury. This review showed that most of the studies conducted in different countries on heavy metals were mostly in red meat, and the research was few in the cases of domesticated birds and very rare in game birds, although it is considered a good example for investigating heavy metals in the environment